(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless Sensor Networks (WSN) are one of the most rapidly developing technologies with a wide range of applications which includes a sensing process, security providence and environmental sensing and military applications. WSN consists of collection of sensor nodes and each sensor nodes are used for sensing the environmental conditions while transmitting data to the base station. Energy consumption is the major issue in WSN. Each sensor nodes can utilize only limited amount of power supply for performing transmission of packets in a wireless environment. In this paper, we study the various routing protocols and compare among them. We also study the trade-offs between energy and communication overheads, highlighting the advantages and demerits of each routing protocol with the purpose of discovering new research Directions. Based On The Identified ResearchGap,WePropose An Optimum Energy Efficient Routing Protocol For Today’s Wsns. Clustering is one of the promising techniques for reducing the energy consumption. In a clustered WSN, sensor nodes are partitioned into a certain number of clusters, each of which has a cluster head (CH) and some non-cluster head members. CH collects information from all the cluster members and then forwards to other CH. while non-CHs are responsible for sensing environmental conditions and transmitting information to the corresponding CH. The simulation results show how the election criteria for cluster heads election such as random election and nodes with different energy level affect the number of cluster heads elected, and the network lifetime. In this paper, we analyse three different types of routing protocols: LEACH, SEP, and TEEN. Simulation results are provided to show the comparative effectiveness of different clustering algorithm on network lifetime and cluster head selection and failure nodes in the network. Sensor networks are simulated using MATLAB simulator.